THE IMPACT OF PRINTING BENEFIT QUALITY, SATISFACTION CUSTOMER AND CLIENT DEPENDABILITY IN EFFORTS TO EXTEND COMMERCE DEALS TURNOVER ANGELA GIFT PRINTING IN SURABAYA - Sofyan Lazuardi; Fanny Dwi Puspitasari; Etin Puspitasari (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
This study aims to clarify the quality of printing services and customer satisfaction can significantly affect Customer Loyalty in an effort to increase sales turnover of printing business angela souvenir surabaya. This research uses quantitative research methods. The population in this study is customers who use angela souvenir surabaya printing services with a sample of 18 respondents, then analysis techniques and using statistics using spss 25.00. to Knowing the results requires Multiple Linear Test, Test F and Test t. Variable quality of print service quality (X1) and customer satisfaction (X2). These have a significant impact on the dependent variable of customer loyalty (Y).  Print quality (X1) and customer satisfaction (X2) scores can affect customer loyalty (Y) by 0.888 indicating that 88.8% of customer loyalty variables and the remaining 11.2% are not explained by other variables. Print Service Quality (X1) t count (3,759) t table (2,131) with significance level 0.002 0.05.Customer Satisfaction (X2)t count (3,181)t table (2,131) with a significance level of 0.006 0.05. That partially The Quality of Print Services and Customer Satisfaction (X2) significantly affects Customer Loyalty (Y) in an effort to increase sales turnover at Angela Souvenir Printing in Surabaya.